Genetic Variants Related to Coffee Consumption and Their Association with Obesity Risk: A Systematic Review - Ajmain, Nabilatulkhilwa Khairi; Teh, Lay Kek; Rahman, Thuhairah Hasrah Abdul; Ghani, Rohana Abdul; Nor, Norazmir Md; Seow, Lay Jing; Dewanti, Beauty Suestining Diyah; Huda, Nurul; Seow, Eng Keng (Department of Technology of Agricultural product (THP) Jambi University, 2026)
Coffee consumption has been associated with metabolic health and obesity risk, potentially through bioactive compounds that influence energy metabolism. Genetic variation may partly explain interindividual differences in these effects, yet the population-specific relevance of such variants remains unclear. However, the population-specific relevance of these genetic variants remains insufficiently explored. OBJECTIVES: This systematic review synthesizes genetic variants associated with coffee consumption and obesity susceptibility across ethnically diverse populations and validates their relevance in global populations using public genomic databases. METHODS: A comprehensive literature search was conducted in PubMed, Scopus, Web of Science, and Google Scholar to identify genome-wide association studies and candidate gene studies examining genetic variants related to coffee consumption, caffeine metabolism, and obesity-related traits. Identified variants were cross-referenced with dbSNP and the GWAS Catalog to assess allele frequency distributions and genomic support. Study quality was evaluated using the National Institutes of Health assessment tools for observational studies. RESULTS: The review identified genetic variants involved in caffeine metabolism (POR, ALDH2, GCKR), neuroregulation and appetite control (BDNF), taste perception (TAS2R38, CA6), adipokine regulation (KNG1), dietary fat response (APOA2), and obesity susceptibility (MC4R, ARL15). Public genomic database analyses suggest that several variants are consistently observed across global populations, supporting their potential generalizability. CONCLUSION: This review highlights the broad population-genetic predispositions underlying the relationship between coffee consumption and obesity risk and supports the need for future research that integrates multi-omics approaches with in vivo and in vitro models to elucidate the biological mechanisms of coffee-related genetic variation.